Resource-constrained project scheduling with ant colony optimization algorithm - Niken Anggraini Savitri; I Nyoman Pujawan; Budi Santosa (Journal of Civil Engineering, 2020)
Resource allocation commonly becomes one of the critical problems in project scheduling. This issue usually occurs because project managers estimate the schedule of activities and network time without considering resource availability. Resource-Constrained Project Scheduling Problem (RCPSP) links to the allocation of resource or set of resources into certain activities in order to accomplish particular objectives. Various approaches have been performed to overcome RCPSP, including the heuristic approach. In this research, we used the Ant Colony Algorithm in solving RCPSP. We used 11 examples of projects with dissimilarity in-network and several activities. The implementation of the Ant Colony Algorithm resulted in the percentage of a near-optimal solution of 63.64%. Besides, the duration obtained from the algorithm above the manual scheduling (assumed optimal) was only 4.29%. Sensitivity analysis was performed to understand how substantial the changes of ACO parameters influenced the result obtained from the algorithm. Based on the result, we could conclude that the parameters of ACO have no significant effect to project duration.